2013
DOI: 10.3928/21650799-20130816-52
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Caregiver Forces Required for Sliding a Patient Up in Bed Using an Array of Slide Sheets

Abstract: This study investigated the forces required while performing the common patient handling task of moving a patient up in bed using traditional cotton sheets or friction-reducing slide sheets. Twenty-nine healthy adult participants 18 to 36 years of age were recruited as "patients." Hand forces and lumbar compression and shear forces were calculated on the "caregiver" when performing the repositioning task. Significant differences in lumbar compression and lumbar sagittal shear forces at L4-L5 and at L5-S1 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 16 publications
1
17
1
Order By: Relevance
“…They found a decrease in the peak torque and compression force at the L4/L5 joint when using friction-reducing devices for repositioning a supine patient toward the head of the bed. Similar conclusions were obtained by Bartnik and Rice (2013) who investigated the force required for moving a patient upward in bed using frictionreducing slide sheets versus traditional cotton sheets, which was reduced with the sliding sheet.…”
Section: Impact On Upper and Lower Back Pain And Disabilitysupporting
confidence: 75%
See 3 more Smart Citations
“…They found a decrease in the peak torque and compression force at the L4/L5 joint when using friction-reducing devices for repositioning a supine patient toward the head of the bed. Similar conclusions were obtained by Bartnik and Rice (2013) who investigated the force required for moving a patient upward in bed using frictionreducing slide sheets versus traditional cotton sheets, which was reduced with the sliding sheet.…”
Section: Impact On Upper and Lower Back Pain And Disabilitysupporting
confidence: 75%
“…Lloyd and Baptiste's (2006) laboratory study concurs with our findings, showing significantly lower force on the upper extremities during the performance of transfer tasks using friction-reducing equipment compared with regular draw sheets. Bartnik and Rice (2013) also found a reduction in the force required by the caregiver's hands to pull a patient up in bed when using friction-reducing sliding sheets. Accordingly, it may be concluded that the use of a sliding sheet has a protective influence on arms, shoulders, and hands expressed after a prolonged period of time.…”
Section: Influence On Arms Shoulders and Hand Pain And Disabilitymentioning
confidence: 91%
See 2 more Smart Citations
“…A slide is a small auxiliary device used to transport a patient or move a patient from the bed to a wheelchair. Some studies support the use of slides as a part of musculoskeletal injury prevention programs as they can reduce the risk of musculoskeletal injuries for nurses [54,55]. However, the current study showed a considerably low usage rate of slides (once every 2 days) among the ICU nurses.…”
Section: Discussioncontrasting
confidence: 53%